FACEBOOK WRITTEN LEVANTINE VERNACULAR LANGUAGES - Abu Elhij'a, Dua'a (The Levantine Review, 2012)
Over the last fifteen years, in every Arabic-speaking country, young Arabic speakers have begun to write their spoken language in electronic media, such as Facebook, MSN Messenger, and so on. The new way of writing in social media is a radical deviation from the traditional norm of writing the classical language—as well as what is commonly referred to as Modern Standard Arabic. This study is presenting this phenomenon in the Levant— Jordan, Lebanon, and Israel/Palestine.